An international study of public contact with people who have an intellectual disability. Issue 3 (6th January 2021) - McConkey, R.; Slater, P.; Dubois, L.; Shellard, A.; Smith, A.
Abstract: Background: People with intellectual disability (ID) are often socially isolated, and many experience stigma and discrimination. Increased contact with the general public is thought to overcome prejudices. This large‐scale international study had three main aims: to determine the type and frequency of contact that the general public has with people with ID; to identify the personal characteristics of those who have greater contact; and to examine the public's level of comfort at the prospect of having contact with people with ID. Method: Self‐completed online questionnaires were administered to nationally representative panels of respondents in 17 countries; totally 24 504 persons. Multivariate analyses were used to identify respondents more likely to have had frequent personal contact with persons with ID from those with infrequent or no contact and those respondents who were most comfortable at meeting a person with ID. Results: Internationally around one in four of the general population reports having frequent personal contact with people who have an ID although this varied from 7% in Japan to 46% in Panama. The principal forms of contact were through friendships, neighbours or extended family members. Over all countries, volunteering and engagement with Special Olympics were the two main predictors of frequent personal contact followed by employment in the education, health or social care field, being a parent of children under 18 years, playing sports and being employed. People who reported frequent personal contact were also more comfortable at meeting a person with ID. Conclusions: This international dataset provides a baseline against which public contact can be compared across countries and changes monitored over time. The findings suggest ways in which greater contact can be promoted and making the public more comfortable at meeting people with ID.